Rotenone effects on the human body with reference to neurological disorder - Shreya Singh; Dr. Ruchi Yadav (International Journal of Toxins and Toxics, 2024)
It has been claimed that the well–known neurotoxic pesticide rotenone, which is known to block the mitochondrial complex I, is strongly linked to the pathophysiology and etiology of Parkinson's disease (PD) in humans. There have been numerous analyses in the past and are still being conducted to establish a relationship between the two in order to completely comprehend the level of harm brought on by rotenone. Numerous laboratory studies shown that rotenone exposure results in vivo substantia nigra dopaminergic cell death, which is a hallmark of PD neuropathology. Rotenone also causes α–synuclein to aggregate in vivo, which is another characteristic of the neuropathology associated with PD. Patients with Parkinson's disease have Lewy bodies and Lewy neurons in their brains. In addition, some in vivo models of rotenone mimic the symptoms of Parkinson's disease (PD), including inclusions. Peripheral synuclein and intestinal motility disorders are thought to precede typical PD symptoms, including bradykinesia. Resting Tremor and hardness of the tooth plate. It is thus very important to tackle rotenone toxicity in humans utilizing the available advanced technologies and approaches. Through this study, we are trying to highlight the havoc that rotenone causes as an attempt to attract the attention of the scientific community.
Keywords: Exposure; Neurotoxic pesticide; Parkinson’s Disease; Rotenone; Toxicity